De spottende vraag waar God is: een motief in het boek der Psalmen - Veld, B. van't (Theologia reformata, 2026)
In Psalms 42:4; 79:10 and 115:2 plaintiffs are confronted with the painful question, "Where is your God?" They nevertheless confidently cling to him. Fundamental to this confidence is the name YHWH as a reference to God’s active presence with Israel (cf. Ex. 3:14-15). Therefore, absence of God is not to be understood in an absolute sense, but as a lack of response to a present need. The plaintiffs trust that God is present in the background of their existence; he will not abandon them in the end. God is far and yet near, absent and yet present (cf. Rom. 8:38-39).